2000
DOI: 10.1002/1099-0879(200011)7:5<379::aid-cpp242>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder following high- and low- magnitude stressors in psychotherapeutic inpatients

Abstract: High-magnitude stressors and posttraumatic stress disorder (PTSD) are frequently in psychiatric patients. In contrast, the role of low-magnitude stressors has rarely been studied. We assessed a consecutive series of 78 psychiatric inpatients taking part in our psychotherapy programme for potentially traumatic events and PTSD with a structured interview. All participants completed self-report questionnaires on PTSD-symptomatology, dissociative and general psychopathology (DES, SCL-90). A distressing event was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 15 publications
1
12
1
Order By: Relevance
“…Of those who experienced an event, the proportion that were categorised as traumatic varied from 66.7% using the unanimous method to 80.2% using rater 1's interpretation and classification of events. In previous studies, the proportion of events that has been classified as Criterion-A1 has ranged from 36% to 85% using various methods and samples (Gold et al, 2005;Hovens & Van der Ploeg, 1993;Mol et al, 2005;Roemer et al, 1998;Spitzer et al, 2000). It is likely that the current study was at the higher end of this spectrum as it employed a sample that had been disproportionately exposed to a natural disaster, a trauma typically classified as a Criterion-A1 event in the scientific literature.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Of those who experienced an event, the proportion that were categorised as traumatic varied from 66.7% using the unanimous method to 80.2% using rater 1's interpretation and classification of events. In previous studies, the proportion of events that has been classified as Criterion-A1 has ranged from 36% to 85% using various methods and samples (Gold et al, 2005;Hovens & Van der Ploeg, 1993;Mol et al, 2005;Roemer et al, 1998;Spitzer et al, 2000). It is likely that the current study was at the higher end of this spectrum as it employed a sample that had been disproportionately exposed to a natural disaster, a trauma typically classified as a Criterion-A1 event in the scientific literature.…”
Section: Discussionmentioning
confidence: 70%
“…In contrast, most other studies have reported similar or greater mean PTSD scores and/or PTSD prevalence in individuals reporting non-traumatic life events compared to those who report Criterion-A1 events (Bodkin, Pope, Detke, & Hudson, 2007;Gold et al, 2005;Mol et al, 2005;Solomon & Canino, 1990;Spitzer et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Although their results were supportive of this premise, once variables such as time since the event, depression and perceived stress, were controlled for, A1 events were no longer associated with PTSD symptoms. Other studies have demonstrated that individuals who have experienced qualifying events do not report any more PTSD symptoms than those who experienced non-A1 events (e.g., Green et al, 2000;Spitzer et al, 2000), whereas other researchers have shown non-traumatic events to be associated with greater levels of PTSD symptoms than qualifying events (e.g., Gold et al, 2005;Long et al, 2008). A similar study using a large community sample in the Netherlands also reported greater prevalence of PTSD symptoms among those experiencing non-A1 events (Mol et al, 2005).…”
Section: Research Into Frequency and Severity Of Ptsdmentioning
confidence: 99%
“…The most important trauma should be identified in collaboration with the patient. This depends on qualitative impact of the stressor on the individual rather than its magnitude [45]. Least but not last, we hypothesize that the patients' position as both a subject and an object of psychotherapy is closely related to the concept of resistance.…”
Section: Case Examplementioning
confidence: 99%